ETNOLINGUISTIK, SEBUAH KAJIAN ANTROPOLOGI MASYARAKAT BANJAR DI PASAR TERAPUNG LOK BAINTAN KABUPATEN BANJAR KALIMANTAN SELATAN - Mufidah, Nida (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2014)
This paper is a study antropolinguistic with behavioral problems speaking, the characteristics of linguistic and cultural representation in the language of a question to take a place at the Floating Market Lok Lok Baitan located Baintan River District village of Tabuk Banjar District, South Kalimantan. Floating Market is a traditional market held on a tidal river. The method used is the method entholinguistic, coupled with the techniques developed in other subject areas, such as: the development of pragmatics, conversation analysis, participatory observation, interviews and recording. Linguistic evidence found in this study with regard to terminology: (1) the floating markets, (2) boats and kelotok, (3) transaction, (4) the propriety of the transaction, and (5) form of address.